#TITLE_ALTERNATIVE# - MAHARDIKA FORENTIN NIM: 20716011, ALFIAN
Reteplase recombinant is a recombinant plasminogen activator (rPA) of alteplase derivatives used as thrombolytic for the treatment of acute myocardial infarction. Reteplase has been approved by FDA and EMA since 1996. However, reteplase has never been produced or marketed in Indonesia until now and has an expensive price. Reteplase is produced in Escherichia coli and tends to form inclusion body because it has nine disulfide bonds. The objective of this study was to optimize the dissolved reteplase production process using pET24b expression vector in E. coli BL21(DE3), to examine the activity and purify it with Ni-NTA affinity chromatography. Synthetic DNA coding codon optimized reteplase was brought by plasmid pET24b and referred as pET24b_ret. The production of reteplase was performed in recombinant E. coli BL21(DE3) carrying the plasmid with and without a pGroElDnaK chaperone plasmid. The recombinant E. coli was confirmed by the validity of itÃ‚Â’s carried plasmid through the restriction analysis and sequencing of DNA encoding reteplase, GroEl and DnaK. Optimization of overproduction condition of reteplase protein was done by modify the temperature (20, 25, 37 and 40Ã‚Â°C), Luria Bertani media composition (LB and Ã‚Â¼LB) and expression of reteplase in E. coli BL21(DE3) with or without pGroElDnaK. The culture was induced by isopropylthio-β-D-galactoside with a final concentration of 0.05 mM at OD600 of 0.7-0.8. The overproduced reteplase was characterized using SDS-PAGE and analyzed with ImageJ software. Reteplase activity was determined with a tPA human chromogenic activity assay. The soluble form of produced reteplase was 1.14 Ã‚Â± 0.01 mg/g of wet cells and provided an activity of 45.97 IU/mg crude reteplase using production conditions at 20Ã‚Â°C in recombinant E. coli without chaperones in LB media. While the highest insoluble of reteplase was produced at 37Ã‚Â°C in recombinant E. coli without chaperones in LB media that resulting 19.6 Ã‚Â± 1.6 mg protein/g wet cells. The insoluble form of reteplase was successfully dissolved by 8 M urea, 0.1 M DTT in 50 mM pH 8 buffer Tris-Cl, and giving activity of 1.53 IU/mg crude reteplase but did not bind to Ni-NTA column. It can be concluded that reteplase can be produced in the active form using a plasmid pET24b_ret expression in E. coli BL21(DE3).